Scientific Approach to Learning Fiqh in Madrasah Tsanawiyah - Nicky Estu Putu Muchtar (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
This study aims to describe learning based on scientific learning in fiqh subjects at Madrasah Tsanawiyah. The method used is descriptive qualitative. Data collection techniques using observation and interviews. As for the analysis using written data techniques. This article produces a scientific approach to learning Fiqh in madrasah through the creation of learning designs carried out by Fiqh subject teachers concerning the steps outlined in the scientific application, namely, learner analysis to determine student learning styles and competency levels, learning focuses on student centred, use of various learning methods and media and evaluation based on authentic assessment.